Diversidade de algas verdes em crostas biológicas de solo do cerrado - Tralli, Marcella Palhiari [UNESP] (2015)
Green algae are a higly diversified group and their representatives can be found in many types of habitats. On soils, green algae, in association with other organisms, may form biological crusts, a community considered relevant in some ecosystems (especially in arid and semi-arid environments). They are pioneer in soil systems, helping to reduce erosion by stabilizing and improving the physical and chemical properties of soils and influencing the germination of different plants. This study aims to the taxonomic survey of green algae assemblages found in savannah areas in the states of São Paulo and Minas Gerais. In addition, the comparison of taxonomic compositions of the assemblages from different localities and the molecular characterization of the most frequent species are complementary objetives. The sampled material was directly examined under light microscope and also cultivated on artificial growth media. The results obtained are based on the analyzes of 40 samples collected in April 2013. The taxonomic survey resulted in the finding of 17 morphotypes pertaining to Trebouxiophyceae, Chlorophyceae, Ulvophyceae, Klebsormidiophyceae and Conjugatophyceae. Two out 17 identifications were possible only to the generic level (Chlorococcum sp. and Klebsormidium sp.) due to the absence of reproductive stages. One population was not identified due to the inconsistence of the observed characteristics to identify. Four occurrences are new records for the country. The two study areas showed distinct floristic composition, with only six occurrences common to both parks. The highest species richness was recorded in the Serra da Canastra National Park, with 14 morphotypes, while in the State Park Furnas do Bom Jesus were recorded only seven. Soil nutrients, moisture, temperature and pH have shown that the occurrence of a species cannot be addressed to a single environmental variable, but possibly two or more...